Efektivitas Metode Numbered Head Together untuk Meningkatkan Maharah Kalam Siswa Kelas VII di MTs Mamba'us Sholihin Gresik - andrian, Azril (Jurnal Pendidikan Bahasa Arab, 2025)
Speaking is a basic skill in Arabic language education, but it is often the weakest skill possessed by students, especially in the early grades of junior high school. Observations in first grade "B" at Al-Manba' Al-Salihin Islamic Preparatory School revealed that students had difficulty speaking because most were new students, and their vocabulary was inadequate for daily use. Although some students had memorized many words, their speaking skills remained weak due to lack of practice. To address this problem, this study chose the Numbered Heads method as a collaborative learning strategy aimed at increasing students' confidence in speaking Arabic. This study aimed to determine how the Numbered Heads method could be applied to improve the speaking skills and effectiveness of first grade students in class "B" at Al-Manba' Al-Salihin Islamic Preparatory School in Suji Maniyar Garsik. A qualitative approach was used, and the type of research was classroom action research conducted over two sessions. Each session consisted of four phases: (1) planning, (2) implementation, (3) observation, and (4) reflection. The results of the study showed that the application of the Numbered Heads method successfully improved students' speaking ability, as evidenced by the increase in their average scores. The difference in scores between the pre-test and the test in the first session was 11.80, and the difference in scores between the first and second sessions was 12.09.